Women’s Experiences of Immigration Detention in Italy: Examining Immigration Procedural Fairness, Human Dignity, and Health - Esposito, Francesca; Di Martino, Salvatore; Briozzo, Erica; Arcidiacono, Caterina; Ornelas, Jose (Frontiers in Psychology, 2022)
Recent decades have witnessed a growing number of states around the world relying on border control measures, such as immigration detention, to govern human mobility and control the movements of those classified as “unauthorised non-citizens.” In response to this, an increasing number of scholars from several disciplines, including psychologists, have begun to examine this phenomenon. In spite of the widespread concerns raised, few studies have been conducted inside immigration detention sites, primarily due to difficulties in gaining access. This body of research becomes even scanter when it comes to the experiences of detained women. This study is the first of its kind to have surveyed 93 women confined in an Italian immigration detention facility. A partial mediation model with latent variables was tested through partial least structural equation modelling (PLS-SEM). The findings revealed the negative impact that unfair immigration procedures have on detained women’s human dignity, which in turn negatively affects their self-rated physical and mental health. Overall, our study sheds light on the dehumanisation and damage to human dignity that immigration detention entails, as well as its negative impact on the health of those affected. This evidence reinforces the image of these institutions as sites of persistent injustice, while stressing the need to envision alternative justice-oriented forms to address human mobility.